If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2n + -3) = 5n + 9 Reorder the terms: 4(-3 + 2n) = 5n + 9 (-3 * 4 + 2n * 4) = 5n + 9 (-12 + 8n) = 5n + 9 Reorder the terms: -12 + 8n = 9 + 5n Solving -12 + 8n = 9 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -12 + 8n + -5n = 9 + 5n + -5n Combine like terms: 8n + -5n = 3n -12 + 3n = 9 + 5n + -5n Combine like terms: 5n + -5n = 0 -12 + 3n = 9 + 0 -12 + 3n = 9 Add '12' to each side of the equation. -12 + 12 + 3n = 9 + 12 Combine like terms: -12 + 12 = 0 0 + 3n = 9 + 12 3n = 9 + 12 Combine like terms: 9 + 12 = 21 3n = 21 Divide each side by '3'. n = 7 Simplifying n = 7
| 9/4/2 | | -6+r=49 | | .3x-4=.1(x-10) | | 8c+2(3+c)=46 | | -20u^4-17u^2-3=0 | | -42=q-15 | | 50-2X=100-7x | | f(x-1)=13 | | 9+2a+1=3a-8 | | 4x-22=62+2x | | -z+1=2-3y-x | | 3(x-2)-4(x+4)=-2(x-6) | | -14+3(x+10)=7(2x+5)-4 | | -7(6-7b)+6=-134 | | Z-2-3y=2x | | 6x-18=5x+15 | | h-49=13.8 | | 3x-1=7-3y+2 | | 16+144t+324t^2=0 | | 3(x-20)-4(x+4)=-2(x-6) | | 4c(a-6)+7(a-6)= | | X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 | | 2x+6(1+5x)=230 | | (2x-7/4)=0 | | 25=k/5;k=5 | | x-3+2x=33 | | 8-5x=42 | | -2(3-5k)=-76 | | -5p-3(-p)-p=4 | | -7(x-7)=-84 |